Elevated 2HG does not cause features of tumorigenesis. (15th October 2021) - Adam, Julie; Finch, Alina; Sepulveda, Catarina; Ducker, Martin; Torroba, Maria Blanca; Krell, Daniel; Kriaucionis, Skirmantas; Szele, Francis; Ratcliffe, Peter; Soga, Tomoyoshi; Kranc, Kamil; Tomlinson, Ian; et al.
Abstract: Aims: Gliomas are the most frequent brain tumours, representing 75% of all primary malignant brain tumours in adults. IDH1 (and IDH2) driver mutations occur in >80% of low grade gliomas and secondary GBMs, in <10% of primary GBMs and other cancers. How IDH1/2 mutations contribute to tumorigenesis is mostly unknown. IDH1/2 convert isocitrate to α-ketoglutarate, but when mutated possess a novel enzymatic function that reduces α-ketoglutarate to D2-hydroxyglutarate (2HG). Indeed 2HG accumulates in IDH1/2-mutant tumours, and this discovery suggested that 2HG may have a role in IDH1/2-mutant tumours onset and progression, possibly by causing dysregulations of various enzymes in the cells. Studies are undergoing to clarify the causative role of 2HG in IDH1/2-mutant tumours, but it is still not clear whether 2HG is the driver/oncometabolite. Our aim is to understand the role of 2HG in developing and adult mouse tissues and whether its accumulation might cause features of gliomagenesis. Method: A constitutive D2hgdh Knock-out mouse (D2hgdh KO) was generated and the relative molecular and cellular analysis were performed. Results: Brains dissected from D2hgdh KO mice appeared to be histologically normal. No differences were found in the proliferation and labelling retaining capacity of neural stem and progenitors cells (NSC/NPC) of the D2hgdh KO mice compared to controls. A comprehensive metabolites analysis showed that D2hgdh KO mouse accumulated 2HG in various organs and tissues, included total brains and in the NSC/NPC microdissected from the subventricular zone, the site of origin of many human gliomas. The DNA amount of 5mC and 5hmC extracted from brains of D2hgdh KO mice was similar to controls. A normal number of haematopoietic progenitors was also found. Conclusion: Although D2hgdh KO mice accumulated 2HG in all tissues analysed, they did not develop any abnormalities and remained completely asymptomatic. This suggests that a mere increment of 2HG in developing and adult tissues may be not sufficient to cause tumorigenesis (and gliomagenesis), leading some doubts on the oncogenic roles of the 2HG in IDH1/2-mutant tumours.